2013
DOI: 10.1038/jcbfm.2013.131
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CO2 in Air Versus Carbogen for the Measurement of Cerebrovascular Reactivity with Magnetic Resonance Imaging

Abstract: Measurement of cerebrovascular reactivity (CVR) can give valuable information about existing pathology and the risk of adverse events, such as stroke. A common method of obtaining regional CVR values is by measuring the blood flow response to carbon dioxide (CO 2 )-enriched air using arterial spin labeling (ASL) or blood oxygen level-dependent (BOLD) imaging. Recently, several studies have used carbogen gas (containing only CO 2 and oxygen) as an alternative stimulus. A direct comparison was performed between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
3
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 35 publications
(47 reference statements)
3
49
3
1
Order By: Relevance
“…25 Additionally the high oxygen concentrations used in some gas mixtures may cause further complex changes to the BOLD contrast. 26 One study has suggested that there is little difference between breath holding and CO 2 inhalation, although this study used ASL rather than BOLD to assess CVR. 27 This study also found bigger differences between the vasodilatory stimuli it assessed when absolute change rather than percentage change CVR measures were used.…”
Section: Discussionmentioning
confidence: 99%
“…25 Additionally the high oxygen concentrations used in some gas mixtures may cause further complex changes to the BOLD contrast. 26 One study has suggested that there is little difference between breath holding and CO 2 inhalation, although this study used ASL rather than BOLD to assess CVR. 27 This study also found bigger differences between the vasodilatory stimuli it assessed when absolute change rather than percentage change CVR measures were used.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudocontinuous arterial spin labeling data were pairwise subtracted and normalized by M 0 to generate CBF-weighted maps, spatially smoothed to match the BOLD postprocessing (full-width-half-maximum ¼ 3 mm), and CBF was quantified upon application of the solution of the flow-modified Bloch equation assuming a blood-water T 1 reduction from 1.6 seconds to 1.4 seconds (effect of hyperoxia). 26,27 To enable comparison of negative regions between all subjects, BOLD and CBF-weighted maps were co-registered to a 4 mm isotropic Montreal Neurological Institute (MNI) T 1 -weighted atlas.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the more complex and equivocal nature of BOLD signal changes during hyperoxic hypercapnia, it is advocated to perform BOLD CVR mapping using normoxic hypercapnia [40]. However, some ethical committees could be reluctant to allow normoxic hypercapnic challenge rather than hyperoxic hypercapnic challenge, especially in patients referred for stroke and steno-occlusive disease.…”
Section: Discussionmentioning
confidence: 99%